Zombie Apocalypse Holy Land, Haiti, Hollywood - Rey, Terry (Open textbook library., 2024)
Zombie Apocalypse: Holy Land, Haiti, Hollywood explores the intellectual and cultural histories of two highly influential and essentially religious ideas, that of the zombie and that of the apocalypse. The former is a modern idea rooted in Haitian Vodou and its popular African and European religious antecedents, while the latter is an ancient one rooted in Zoroastrianism and the Bible and widely expanded in Judaism, Christianity, and Islam, and is arguably one of the most influential ideas in world history. Today the merger of the zombie and the apocalypse has pervaded popular culture, with the zombie surpassing the vampire and Frankenstein as the most prolific monster in popular American consciousness. Drawing on biblical studies, African studies, Caribbean studies, and the sociology and history of religion, Parts I (Holy Land) and II (Haiti) explore the religious origins of these ideas. Part III (Hollywood) uses aspects of cultural studies, literary analysis, critical race theory, and cinema studies to document the (primarily) American obsession with the zombie and the zombie apocalypse. The apocalypse and the zombie have been momentous intellectual, historical, and cultural realities and social forces in both very ancient and very recent human history and culture. As such, Zombie Apocalypse provides a focused analysis of certain fundamental aspects of human existence. It challenges readers to cultivate their critical thinking skills while learning about two of the most compelling notions in human religious history and the impact they continue to have.